Reference networks and their relevance for managing judicial precedent knowledge in Mexico - Trejo Medina, Daniel (2024)
Effective knowledge management in legal citation networks is vital in the modern practice of law, as it enables more consistent and fair application of judicial precedent, enables informed decision making and supports the law's sustained evolution, especially under technology evolution and pressure from the digital divide. The opportunities to improve and transfigure the practice of law are equally vast., are significant, the opportunities to improve and revolutionize legal practice are equally vast, as we move towards an increasingly digitized future, the ability to effectively manage and utilize legal knowledge will be increasingly valuable, not only to legal professionals, but to the integrity and effectiveness of the justice system.